A new species of Ianthorntonia García Aldrete, from Bolivia, and description of the female Ianthorntonia marshalli García Aldrete (Psocodea: Psocomorpha: Epipsocetae: Epipsocidae) - García Aldrete, Alfonso Neri (EntomoBrasilis, 2017)
Abstract. A species of Ianthorntonia García Aldrete from the Department of La Paz, Bolivia, is here described and illustrated. It is based on a male, and differs from the other five species in the genus on hypandrium and phallosome characters. Also, the female Ianthorntonia marshalli García Aldrete, 2004, collected at the type locality of the species, is described and illustrated. It is the first female known in the genus; as expected, it is similar to the females of Goja Navás and Gojaoides García Aldrete. Uma nova espécie de Ianthorntonia García Aldrete, para a Bolívia, e descrição da fêmea de Ianthorntonia marshalli García Aldrete (Psocodea: Psocomorpha: Epipsocetae: Epipsocidae) Resumo. Uma espécie de Ianthorntonia García Aldrete, proveniente do departamento de La Paz, Bolívia, é aqui descrita e ilustrada. Esta espécie é baseada em um macho e difere das outras cinco espécies deste gênero pelas características do hipândrio e do falossomo. Além disso, a fêmea de Ianthorntonia marshalli García Aldrete, 2004, coletada na localidade tipo desta espécie, é descrita e ilustrada. Esta é a primeira fêmea conhecida para este gênero; como previsto, ela é similar as fêmeas de Goja Navás e Gojaoides García Aldrete.